Syria's Peasantry, the Descendants of Its Lesser Rural Notables, and Their Politics - Batatu, Hanna, 1926- (Book collections on Project MUSE., 1999)
In this book, Hanna Batatu presents a comprehensive analysis of the recent social, economic, and political evolution of Syria's peasantry, the segment of society from which the current holders of political power stem. Batatu focuses mainly on the twentieth century and, in particular, on the Ba'th movement, the structures of power after the military coup d'etat of 1963, and the era of Hafiz al-Asad, Syria's first ruler of peasant extraction. Without seeking to prove any single theory about Syrian life, he offers a uniquely rich and detailed account of how power was transferred from one demographic group to another and how that power is maintained today.